Neural substrates in patients with visual-spatial neglect recovering from right-hemispheric stroke - Cao, Lei; Ye, Linlin; Xie, Huanxin; Zhang, Yichen; Song, Weiqun (Frontiers in Neuroscience, 2022)
Visual-spatial attention disorder after stroke seriously affects recovery and quality of life in stroke patients. Previous studies have shown that some patients recover rapidly from visual-spatial neglect (VSN), but the brain networks underlying this recovery are not well understood. Using functional magnetic resonance imaging, we aimed to identify network differences between patients who rapidly recovered from VSN and those with persistent VSN. The study included 30 patients with VSN who had subacute stroke. Patients were examined 2–4 weeks after stroke onset and 4 weeks after the initial assessment. At the last evaluation, patients in the persistent VSN (n = 15) and rapid recovery (n = 15) groups underwent paper-and-pencil tests. We defined the bilateral frontal eye fields, bilateral intraparietal sulcus in the dorsal attention network, and right temporoparietal junction and ventral frontal cortex areas in the ventral attention network as regions of interest (ROI) and measured whole-brain ROI-based functional connectivity (FC) and amplitude of low-frequency fluctuations (ALFF) in subacute right-hemisphere stroke patients. VSN recovery was associated with changes in the activation of multiple bilateral attentional brain regions. Specifically, persistent VSN was associated with lower FC in the right superior frontal gyrus, right inferior temporal gyrus, right medial orbitofrontal cortex, left precuneus, right inferior parietal gyrus, right medial frontal gyrus, right rectus gyrus, left superior frontal gyrus, left middle cingulate gyrus, right superior temporal pole, right postcentral gyrus, and right posterior cingulate gyrus compared to that in those with rapid recovery, whereas ALFF in the left cerebellum were decreased in patients with persistent VSN. Our results demonstrate that the DAN rather than the VAN, plays a more important role in recovery from VSN, and that the cerebellum is involved in recovery. We believe that our results supplement those of previous studies on recovery from VSN.